Pemberdayaan Ekonomi Masyarakat Melalui Dewan Masjid Indonesia di Kabupaten Tasikmalaya - Anwar Taufik Rakhmat (Jurnal Ilmiah Ekonomi Islam, 2023)
Mosques have an important role in empowering the people in the fields of education, social, and economy. This role involves the manager or organization that manages the mosque. The Indonesian Mosque Council (DMI) is an organization whose goal is to empower the community through the resources they have. The purpose of this study was to get an overview of the concept and implementation of community economic empowerment carried out by the Regional Management (PD) DMI Tasikmalaya Regency. This research was conducted through a qualitative approach. Data collection techniques were carried out through interviews and observations. The interview was conducted in three phases, namely the orientation phase, the work phase and the termination phase. The data analysis used in this research is qualitative research, namely research in which the data is expressed in verbal form and analyzed without using statistical techniques. The economic empowerment of the community through the Indonesian Mosque Council in Tasikmalaya Regency is very optimal. This can be proven from several programs implemented by PD DMI in Tasikmalaya Regency that have succeeded in boosting the economy of the mosque community, through economic digitization programs, economic institution development programs, and mosque economic empowerment programs.